‘Paedophile Hunters’: Practitioner Perspectives - Frampton, Laura (Probation journal, 2023)
The National Police Chiefs’ Council (NPCC) position on Online Child Abuse Activist Groups (OCAGs), more commonly referred to as ‘paedophile hunters’, is that their motivation should be questioned since there is no positive advantage to policing. The problematic nature and inaccuracy of the term ‘paedophile hunter’ will be explored within this article, but the term is widely used in practice. Such activism increases risk to potential victims, the suspect and to the efficiency and effectiveness of criminal justice processes ( NPCC, 2018). The Probation Service (PS) has no formal position regarding the activity. Yet public fascination with those convicted of sexual offences against children and the appetite for naming and shaming these individuals is not a new phenomenon. The rise in popularity of the internet and the surge in content available online is more recent, and so is the problem of threat exceeding capacity. But what are the views of practitioners on this issue? Using in-depth qualitative interviews with police and probation practitioners, this paper examines how ‘paedophile hunting’ activity has become a concept in the management of sexual offending in England and Wales, and for the first time, reveals the views and attitudes of professionals working on the front line.